fun little radical cancellation thingy

Starting with \sqrt[3]{a} +1 = \sqrt[2]{a}:

a + 3\sqrt[3]{a^{2}} + 3\sqrt[3]{a} + 1 = \sqrt[2]{a^{3}}

Substituting \sqrt[2]{a}-1 for \sqrt[3]{a}

I have no idea why the rendering is broken for this line, will fix later:

a+3[\sqrt[2]{a}-1]^{2} + 3[\sqrt[2]{a}-1] + 1 = \sqrt[2]{a^{3}}

a + 3[a-2\sqrt[2]{a} +1] + 3\sqrt[2]{a} -3 +1 = \sqrt[2]{a^{3}}

a + 3a - 6\sqrt[2]{a} +3 + 3\sqrt[2]{a} -3 + 1 = \sqrt[2]{a^{3}}

4a - 3\sqrt[2]{a} + 1 = \sqrt[2]{a^{3}}

4a +1 = \sqrt[2]{a^{3}} + 3\sqrt[2]{a}

What’s amazing here is that if we square both sides, we completely

eradicate all the radicals on the right side (eradicalize!)

viz \sqrt[2]{a^3}\sqrt[2]{a} = \sqrt[2]{a^{4}} = a^{2}

16a^{2} +8a + 1 = a^{3} + 6a^{2} +9a

And you get a single polynomial from this:

a^{3} -10a^{2} +a -1

throwing that into wolfram alpha, we find that

a = \frac{1}{3}\left(10+\sqrt[3]{\frac{1937-33\sqrt[2]{93}}{2}}+\sqrt[3]{\frac{1937+33\sqrt[2]{93}}{2}}\right)

Advertisements

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s